Comparison of SYBR Green and TaqMan real-time PCR methods for quantitative detection of residual CHO host-cell DNA in biopharmaceuticals. Issue 2 (March 2015) - Soltany-Rezaee-Rad, Mohammad; Sepehrizadeh, Zargham; Mottaghi-Dastjerdi, Negar; Yazdi, Mojtaba Tabatabaei; Seyatesh, Neda
Abstract: The Chinese hamster ovary (CHO) cell line is one of the predominant hosts used in the bioproduction of pharmaceutical proteins. There have been many concerns about the use of animal cell lines in biopharm industries, and one of the most important concerns has been residual host-cell DNA. Improper integration of residual DNA into the recipient genomes could activate oncogenes or deactivate tumor suppressor genes. Real-time polymerase chain reaction (PCR) is a routine assay method used in the quantification of DNA. In this study, genomic CHO DNA was purified and subjected to real-time PCR. The efficiency of the reaction was calculated, and the limit of detection (LOD) was determined. The calculated efficiency for the primers using the SYBR Green method was 94.3% ( r 2 = 0.998). A melting curve analysis showed neither unspecific products nor primer dimers. The calculated efficiency for the TaqMan assay was 96.6% ( r 2 = 1). The results showed that the LOD of the SYBR Green and TaqMan assays were 100 fg and 10 fg, respectively. Since the LOD of the TaqMan assay showed a better sensitivity than the SYBR Green, this method could be used directly on the final products for the quantification of residual DNA, without prior DNA extraction.